2016
DOI: 10.1186/s12913-016-1826-3
|View full text |Cite
|
Sign up to set email alerts
|

Are performance indicators used for hospital quality management: a qualitative interview study amongst health professionals and quality managers in The Netherlands

Abstract: BackgroundHospitals are under increasing pressure to share indicator-based performance information. These indicators can also serve as a means to promote quality improvement and boost hospital performance. Our aim was to explore hospitals’ use of performance indicators for internal quality management activities.MethodsWe conducted a qualitative interview study among 72 health professionals and quality managers in 14 acute care hospitals in The Netherlands. Concentrating on orthopaedic and oncology departments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 21 publications
5
24
0
6
Order By: Relevance
“…14 These doubts over the reliability of data on quality indicators is unlikely only to be an issue at the level of individual healthcare professionals, but also at the organizational level. Here, Botje and colleagues 44 observed that, at times, hospitals estimate levels of compliance to be 100% merely because a protocol is present. Combined with our findings, this raises significant questions over the justification of registering such information.…”
Section: Discussionmentioning
confidence: 97%
“…14 These doubts over the reliability of data on quality indicators is unlikely only to be an issue at the level of individual healthcare professionals, but also at the organizational level. Here, Botje and colleagues 44 observed that, at times, hospitals estimate levels of compliance to be 100% merely because a protocol is present. Combined with our findings, this raises significant questions over the justification of registering such information.…”
Section: Discussionmentioning
confidence: 97%
“…This is particularly important when payments are based on performance. Health care providers view performance as a measure of their ability to provide services and a means to increase their revenues . Evidence suggests that financial rewards such as bonuses resulting from P4P is a key factor influencing provider behaviour .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we want to test if perceived patient safety corresponds with objective non-disease-specific patient-safety and quality-of-care measures available in routine data. By doing so, we add to the limited existing literature concerning performance quality has rarely been linked to staff perceptions [42, 43]. Correlations between workload and patient outcomes or patient safety have mostly been assessed for specific diseases like hip fracture and myocardial infarction [44, 45].…”
Section: Introductionmentioning
confidence: 99%